Analysis of the effect of repair welding/grinding on the performance of railway crossings using field measurements and finite element modeling. (March 2018) - Xin, Lizuo; Markine, Valeri; Shevtsov, Ivan
In this paper, the effects of repair welding and grinding, which are currently the main components used in the maintenance of crossings, on the performance of crossings are analyzed. It has been observed that sometimes the welding and grinding activities that directly affect the geometry of the crossings and/or material properties can have negative effects on the performance and ultimately on the service life of the crossings. In this paper, the effect of the changes of geometry has been studied experimentally, while the effect of the changes in the material properties has been analyzed using a numerical model. When grinding the shape of the crossing nose, the resulting profile can deviate from the original one. To analyze the geometry-related effects of welding and grinding, the geometry of crossings (cross-sectional profiles) as well as the corresponding dynamic accelerations due to passing trains are measured before and after the welding and grinding activities. Based on the comparison of the measured accelerations, the performance of the measured crossings has been assessed. Also, a welding repair that is not properly performed can lead to undesirable changes in the material properties of the rails, resulting in defects in rails. The material-related effects of the welding and grinding are studied using the three-dimensional explicit finite element model wherein a wheelset moves over a railway crossing. To understand the microstructure of the welding defect and provide an input for the numerical model, the results of ultrasonic and microscopic analyses of some welded crossings are presented first. Then, a number of the numerical simulations of the crossing with the welding defect are performed to investigate the failure mechanism of the crossing. Furthermore, assessment using the fatigue model (coupled with the finite element model) that accounts for the ratcheting behavior of material by calculating a number of the load cycles to the crack initiation is performed. Finally, conclusions on the effects of changes in geometry and material of the crossings due to repair welding and grinding are given.